Dissimilar metal weld failure of steam piping in a hydrogen unit of petroleum refinery. (April 2022) - Subramanian, Chidambaram
Highlights: Steam piping in hydrogen unit was failed after six months of service. Dissimilar weld obtained between SA335 P22 and SA312 TP304L materials directly by type 308L. Low cycle thermal fatigue was a failure mode that initiated from outer wall surface of pipe. Improper filler metal was employed at interface layer and violation of ASME codes & standards were evidenced during dissimilar pipe welding. Type 309/309L filler metal is suggested to prevent dissimilar metal weld failure. Abstract: Steam generation from hot reformer effluent in a hydrogen unit of a petroleum refinery increases the refinery margin. Upstream and downstream piping in hydrogen plant were constructed by SA335 P22 (AS) and type SS304L (SS) materials, respectively. This paper reports failure of dissimilar pipe weld after six months of high pressure steam service. Visual inspection indicates several ratchet marks initiated from outer wall surface at heat affected zone (HAZ) of AS pipe accompanied with brittle fracture. Further, failed samples were examined for chemical analysis, micro-hardness, fractography & elemental analysis and microstructural analysis. Fractographic results indicated that the dissimilar weld was failed due to thermal fatigue. Moreover, microstructural analysis revealed the presence of martensite in AS HAZ region with higher micro-hardness. In-spite of fixed operating temperature at 600 °C, there was a difference in thermal expansion that induced large strain gradient at interface and result in low cycle thermal fatigue failure. Type 308L filler metal was directly employed for dissimilar welding without buttering at interface layer was the main cause of failure. The principal factors that were responsible for Dissimilar Metal Weld (DMW) failure are discussed with respect to Schaeffler diagram and correct welding procedure for failure prevention is proposed. It is further recommended to employ 309/309L filler metal at interface layer according to ASME codes & standards to avoid DMW failure.